2015
DOI: 10.1681/asn.2014111067
|View full text |Cite
|
Sign up to set email alerts
|

Deep Sequencing in Microdissected Renal Tubules Identifies Nephron Segment–Specific Transcriptomes

Abstract: The function of each renal tubule segment depends on the genes expressed therein. High-throughput methods used for global profiling of gene expression in unique cell types have shown low sensitivity and high false positivity, thereby limiting the usefulness of these methods in transcriptomic research. However, deep sequencing of RNA species (RNA-seq) achieves highly sensitive and quantitative transcriptomic profiling by sequencing RNAs in a massive, parallel manner. Here, we used RNA-seq coupled with classic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

42
480
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 479 publications
(544 citation statements)
references
References 38 publications
42
480
2
2
Order By: Relevance
“…activating DHHCs (41). We examined whether an ENaC-activating DHHC (DHHC 3) is expressed in principal cells of the mouse ASDN, where ENaC and aquaporin 2 are localized.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…activating DHHCs (41). We examined whether an ENaC-activating DHHC (DHHC 3) is expressed in principal cells of the mouse ASDN, where ENaC and aquaporin 2 are localized.…”
Section: Resultsmentioning
confidence: 99%
“…We also observed a decrease in TER after treatment of mCCD cl1 cells with 2-BP, which may reflect reduced palmitoylation of claudins normally found within the tight junctions (54 -56). Transcripts for 13 claudins were identified in dissected rat kidney CCDs by deep sequencing (41). A role of claudin palmitoylation in modifying TER was noted in studies of polarized Madin-Darby canine kidney cells, where TER was increased 5-fold after transfection with wild type claudin-14.…”
Section: With Radiolabeling With [mentioning
confidence: 99%
“…Using the protein atlas 59 and Illumina Body Map (GEO: GSE30611), we found that the reproductive tract and the kidney both have intermediate expression of MANBA (not shown), and MANBA is expressed in lysosome of kidney tubule cells ( Figure 4A). 60 Segment-specific expression data obtained from rat kidneys 61 indicate that Manba is expressed in the loop of Henle, with the highest expression level in medullary collecting duct segment.…”
Section: Analysis Of Manba Gene Expressionmentioning
confidence: 99%
“…All 14-3-3 isoforms, except , were detected in mouse kidney and mpkCCD 14 cells. The absence of corresponds with recent large scale RNA sequencing studies of isolated kidney segments from rat (12) or cDNA arrays of isolated rat IMCD (39). Although redundancy among 14-3-3 isoforms has been debated (40), 14-3-3⑀, -␤, -, and -had distinct distributions in mouse IMCD cells, suggesting that different isoforms fulfill different roles in these cells.…”
Section: Discussionmentioning
confidence: 99%
“…Refs. [11][12][13], including the principal cells of the kidney collecting duct (14). The primary functions of these cells are to regulate NaCl (via the epithelial sodium channel, ENaC) 2 and water (via the water channel aquaporin-2, AQP2) transport from the preurine back to the blood and help maintain body NaCl and water homeostasis.…”
mentioning
confidence: 99%